Possible Potential Effects of Honey and Its Main Components Against Covid-19 Infection. Issue 1 (30th March 2021) - Abedi, Farshid; Ghasemi, Saeedeh; Farkhondeh, Tahereh; Azimi-Nezhad, Mohsen; Shakibaei, Mehdi; Samarghandian, Saeed
Coronavirus disease 2019 (COVID-19) is a viral pneumonia that is spreading rapidly worldwide. The main feature of this disease is a severe acute respiratory syndrome and caused by coronavirus 2 (SARS-CoV-2). There are several unknowns about the pathogenesis and therapeutically treatment of COVID-19 infection. In addition, available treatment protocols have not been effective in managing COVID-19 infection. It is proposed that natural anti-oxidants such as lemon, green tea, saffron, curcuma longa, etc. with high flavonoids like safranal, crocin, crocetin, catechins, resveratrol, calebin A, curcumin have therapeutic potential against viral infections. In this context, honey and its main components are being investigated as an option for patients with COVID-19. The present study may indicate that honey and its main components inhibit the entry of the virus into the host cell and its replication as well as modulate the inflammatory cascade. This review provides basic information for the possible potential effects of honey and its main components for fighting with SARS-CoV-2.